2020
DOI: 10.1155/2020/7234218
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Textile Dyes by Chemically Treated Sawdust of Acacia: Kinetic and Equilibrium Studies

Abstract: Sawdust of acacia tree has been successfully used to remove textile dyes from wastewater due to its good sorption properties and its good chemical stability. Two materials are prepared by chemical treatment, including acidic and basic sawdust of acacia. The biosorption tests were carried out on two synthetic dyes of textile which are methylene blue (MB) and brilliant blue (BB). Efficient removal of the both dyes has been achieved by the basic treated sawdust acacia. The modeling of biosorption kinetic shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…We observed that the R 2 coefficients determinedfor the pseudo-firstorder model were higher than the pseudo-second-order model values for this nanohybrid adsorbent. In addition, the computed equilibrium uptakes of the pseudo-first-order (PFO) expression are closer to the experimental values, thus indicating the applicability of this model, which can describe very well the Az sorption process onto Ni/Zn LDH nanoadsorbent via a physical sorption [57].…”
Section: Fitting Kinetic Modelssupporting
confidence: 58%
See 1 more Smart Citation
“…We observed that the R 2 coefficients determinedfor the pseudo-firstorder model were higher than the pseudo-second-order model values for this nanohybrid adsorbent. In addition, the computed equilibrium uptakes of the pseudo-first-order (PFO) expression are closer to the experimental values, thus indicating the applicability of this model, which can describe very well the Az sorption process onto Ni/Zn LDH nanoadsorbent via a physical sorption [57].…”
Section: Fitting Kinetic Modelssupporting
confidence: 58%
“…Hence, the choice of best isotherm fit was conductedby linear regression analyses and a comparison of their correlation coefficients (R 2 ). In addition, the computed equilibrium uptakes of the pseudo-first-order (PFO) expression are closer to the experimental values, thus indicating the applicability of this model, which can describe very well the Az sorption process onto Ni/Zn LDH nanoadsorbent via a physical sorption [57].…”
Section: Adsorption Isotherm Studiessupporting
confidence: 58%
“…Mostly activated carbon is prepared from it which has been used for the removal of different types of dyes from aqueous solutions previously. Comparison of current adsorbent adsorption potential with previously used adsorbents described in literature is shown in Table 5[31][32][33][34]. From data in the table, it is evident that its adsorption capacity is…”
mentioning
confidence: 91%
“…A comparison of present adsorbent capacity with the reported one in literature is given in Table 5. However, one must not be confused about its low adsorbent capacity value as activated carbon being used in the cited studies have a high surface area as compared to our present adsorbent [23][24][25]. The activated sawdust effectively removed the selected dye from water.…”
Section: Comparison Of Adsorption Capacities Of Present Adsorbent With Those Reported In Literaturementioning
confidence: 87%